Structure and dynamics of small polyimide oligomers with silicon as a function of aging. Issue 33 (3rd August 2021) - Burdette-Trofimov, Mary K.; Armstrong, Beth L.; Heroux, Luke; Doucet, Mathieu; Sacci, Robert L.; Veith, Gabriel M.
Abstract : Aging of precursor-based polyimide binders is mimicked using UV curing. The age of the binder directly affects polyimide functionality, adsorption behavior, and slurry structure. Abstract : The effect of UV curing and shearing on the structure and behavior of a polyimide (PI) binder as it disperses silicon particles in a battery electrode slurry was investigated. PI dispersant effectiveness increases with UV curing time, which controls the overall binder molecular weight. The shear force during electrode casting causes higher molecular weight PI to agglomerate, resulting in battery anodes with poorly dispersed Si particles that do not cycle well. It is hypothesized that when PI binder is added above a critical amount, it conformally coats the silicon particles and greatly impedes Li ion transport. There is an "interzonal region" for binder loading where it disperses silicon well and provides a coverage that facilitates Li transport through the anode material and into the silicon particles. These results have implications in ensuring reproducible electrode manufacturing and increasing cell performance by optimizing the PI structure and coordination with the silicon precursor.